Ethnophotography of "Kamulyan Country" In Mondosiyo Traditional Ceremony - Feri Ari Fianto; Risman Marah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The creation of this Ethnophotographic work is a form of the importance of photography as an art archive. Ethnophotography is a genre of photography that uses cultural, human and social objects in the process of its creation. This creation process took the object of research of the Mondosiyo traditional ceremony. The Mondosiyo traditional ceremony is a traditional ceremony that is believed and is still carried out by the people of Pancot village. The Mondosiyo traditional ceremony is a traditional ceremony that is thought to and is still carried out by the people of Pancot village. The commemoration of this ceremony was carried out on the Mandasiya Wukuh on Tuesday Kliwon. Some Mondosiyo traditional ceremonies include making Badek water, Cibukan, Gandik, offerings, Tutuk Bende, slaughtering goat jugs, arak-arakan Reog, beating gamelan Tuk Prul, watering gilang stones, and abur-aburan ayam. The series of Mondosiyo traditional ceremonies are passed down from generation to generation oral by the people of Pancot village. This makes some things about the Mondosiyo traditional ceremony begin to disappear. The lack of archives in the form of texts and visuals owned by the people of Pancot village makes one of the backgrounds for creating this work. The Ethnophotographic work of The Land of Kamulyan in the Mondosiyo Traditional Ceremony can be used by the community as an art archive. The thesis of this work of art uses artistic research methods. Artistic research methods place the artist as a scientist. Every creative process that every artist does has different methods. The use of artistic research methods can combine several methods in the process of creation. There are several types of research using artistic research methods. The creation of this work uses research-based study. This method follows the Ethnophotography creation process carried out.